2016
DOI: 10.1002/2016ja022873
|View full text |Cite
|
Sign up to set email alerts
|

Effects of solar and geomagnetic activity on the occurrence of equatorial plasma bubbles over Hong Kong

Abstract: In the present study, the occurrence and characteristics of equatorial plasma bubble (EPB) has been analyzed using the GPS data from continuously operating reference stations network over Hong Kong during 2001–2012. The analysis found maximum EPB occurrences during the equinoctial months and minimum EPB occurrences during the December solstice throughout 2001–2012 except during the solar minimum in 2007–2009. The maximum EPB occurrences were observed in June solstice during 2007–2008, whereas for 2009, EPB occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 74 publications
(155 reference statements)
4
33
0
Order By: Relevance
“…Apart from the nighttime scintillation occurrences, the daytime scintillation occurrences have also been observed all through the period 2009-2014 with relatively small values as compared to nighttime. Similar diurnal occurrences of irregularities were reported by previous workers [Rama Rao et al 2006, Nishioka et al 2008, Singh et al 2016, Kumar et al 2016. The development of post sunset irregularities is governed by mainly two parameters: evening F-layer drift as well as precursor gravity waves in seeding the instability.…”
Section: Diurnal Variation Of Scintillation Occurrencessupporting
confidence: 85%
See 2 more Smart Citations
“…Apart from the nighttime scintillation occurrences, the daytime scintillation occurrences have also been observed all through the period 2009-2014 with relatively small values as compared to nighttime. Similar diurnal occurrences of irregularities were reported by previous workers [Rama Rao et al 2006, Nishioka et al 2008, Singh et al 2016, Kumar et al 2016. The development of post sunset irregularities is governed by mainly two parameters: evening F-layer drift as well as precursor gravity waves in seeding the instability.…”
Section: Diurnal Variation Of Scintillation Occurrencessupporting
confidence: 85%
“…Using the numerical simulation, [Maruyama 1988] showed that the role of inter-hemispheric neutral winds, which is directed from summer hemisphere to winter hemisphere, is to increase the Pedersen conductivity and thereby reducing the growth rate of the R-T instability. This asymmetry is expected to arise by the difference in inter-hemispheric neutral winds strength during two equinoxes [Nishioka et al 2008, Maruyama et al 2009, Mungufeni et al 2016, Kumar et al 2016. The results reported over Indonesia indicated that, asymmetric meridional winds during vernal and autumn equinox periods over Indonesia may provide asymmetric growth of the irregularity and leading to the equinoctial asymmetry [Maruyama et al 2009].…”
Section: Seasonal Occurrencesmentioning
confidence: 97%
See 1 more Smart Citation
“…The occurrence of EPBs depends on many factors such as local time, longitude, season, solar cycle and geomagnetic activity (e.g. Huang et al, 2002;Burke et al, 2004;Magdaleno et al, 2012Magdaleno et al, , 2017Cherniak and Zakharenkova, 2016;Kumar et al, 2016b). Although EPBs are mainly equatorial phenomena, they can extend to higher latitudes along the magnetic field lines (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…At equatorial region, some studies (Bowman 1998;Sobral et al 2002;Su et al 2006;Ray and DasGupta 2007) found that the geomagnetic activity tended to suppress the generation of ESF. However, some researches have suggested that the dependence of magnetic activity varied with latitude, longitude, season and the phase of storm (Sahai et al 2005;Sobral et al 2002;Becker-Guedes et al 2004;Li et al 2010;Kumar et al 2016). Whalen (2002) reported that there was an inverse relationship between the occurrence of ESF and Kp index during equinoxes and December solstice, but no correlation in June solstice.…”
Section: Dependence Of Magnetic Activitymentioning
confidence: 99%